Spectrophotometric Determination of Ni(II) with 2-Acetyl Thiophene Thiocyanate - Lokhande, R.S.; Chaudhary, A.B.; Nirupa, S. (Asian Journal of Chemistry, 2010)
2-Acetyl thiophene thiocyanate (ATT) was synthesized and its characterization was carried out using IR, NMR and elemental analysis. The development of a new method is proposed for the extraction and spectrophotometric determination of Ni(II) at microgram level. The reagent froms a complex with Ni(II) and was extracted in ethyl acetate at pH 10.4 having absorption maxima at 500 nm. Beer's law is obeyed over the range of 2-100 μ/mL of Ni(II). The molar absorptivity is 0.12 x 104 L mol–1 cm–2 and Sandell sensitivity 0.048 μg cm–2. The stoichiometric ratio of the complex was found to be 1 : 2. Interference of the diverse cations and anions has been studied. The method has been applied to commercial and synthetic samples.